Modulation of Solvation Structure and Electrode Work Function by an Ultrathin Layer of Polymer of Intrinsic Microporosity in Zinc Ion Batteries (Small 25/2022). Issue 25 (23rd June 2022) - Heo, Jiyun; Hwang, Young‐Eun; Doo, Gisu; Jung, Jinkwan; Shin, Kyungjae; Koh, Dong‐Yeun; Kim, Hee‐Tak
Abstract : Zinc Ion Batteries In article number 2201163, Dong‐Yeun Koh, Hee‐Tak Kim, and co‐workers report polymer of intrinsic microporosity (PIM‐1) as an ion regulating layer and an interface modulator which can change the solvation structure of Zn 2+ ion and work function of Zn metal. As a result, PIM‐1 enhances the reaction kinetics of the Zn redox reaction and promotes a uniform Zn deposition/dissolution process.